The lawmakers : judicial power and the shaping of Canadian federalism - Saywell, John T., 1929-2011 (Osgoode Society for Canadian Legal History., 2002)
The Canadian Constitution of 1867 as written should have provided the authoritative guide to the law governing the division of powers between the national and provincial governments of Canada, but by the 1940s the federal constitution was a very different document to that composed originally by John A. Macdonald and his colleagues. In this engaging and exhaustive examination of the critical role of the courts? the Judicial Committee of the Privy Council and the Supreme Court of Canada? in shaping Canadian federalism, John Saywell argues that the courts always have and still do 'make law'? law that can be largely subjective and often bears little relationship to the text or purposes of the Constitution. Saywell begins his analysis by offering new evidence and insights on the structure of the 1867 constitution. Relying heavily on the voices of the actors themselves, his analysis moves beyond a simple examination of previously published reports and examines oral arguments before the Judicial Committee, largely from manuscripts, to determine how the Committee interacted with counsel, developed their arguments, and came to their conclusions. Critical of the jurisprudence of the Judicial Committee, which he argues virtually eliminated some of the critical legislative powers of the federal government and destroyed its capacity to act on the economic and social problems of the twentieth century, Saywell credits the Supreme Court with restoring the balance in the federation and strengthening the national government. Comprehensive, ambitious, and detailed, The Lawmakers will be the definitive work on the evolution of the law of Canadian federalism.